Ensuring open access to European, Latin American and Caribbean research: a description of the OpenAIRE and NECOBELAC FP7 Projects - Furnival, Chloe (Association of Librarians and Information Professionals in the Social Sciences, 2010)
Brief article that outlines two Open Access projects, OpenAIRE – Open Access Infrastructure for Research in Europe – and NECOBELAC – Network of Collaboration between Europe and Latin American Caribbean Countries, both of which count on the input and cooperation of team members of the Centre for Research Communications (CRC) at the University of Nottingham.